Treatment for mastalgia in the presence of diffuse mastopathy in female patients during the menopausal transition period - Н. В. Кулагина (Publishing House TRILIST, 2017)
Objective. To evaluate the efficacy and tolerability of Mastodynon® in the treatment of diffuse mastopathy and symptoms of premenstrual syndrome (PMS) in women in the menopausal transition period. Subjects and methods. A clinical prospective, parallel-group, randomized, monocenter, open-label trial with active control was conducted. The trial included 60 patients (mean age, 49.0 ± 3.1 years) who used Mastodynon® or bromocriptine for 24 weeks. Results. Hyperprolactinemia was detected in 63.3% of the women suffering from different forms of diffuse mastopathy in the menopausal transition period. There was a statistically significant decrease in prolactin levels at 24 weeks of treatment with Mastodynon® (Δ -244 ± 95.8 mU/ml) (p < 0.001) and bromocryptine (Δ -226.4 ± 101.5 mU/ml) (p < 0.001). The results of therapy with Mastodynon® were comparable to the efficiency of that with bromocryptine (p > 0.05). Ultrasound mammography revealed positive changes in the breast structure in 67% of the patients with different forms of diffuse mastopathy treated with Mastodynon® and in 43% of those treated with bromocriptine. There was a decrease in the incidence (92% vs 37%; p < 0.001) and severity of mastalgia at month 6 of Mastodynon® treatment, the results of therapy did not differ in the two groups (p > 0.05). Treatment with Mastodynon® in patients with different forms of mastopathy concurrent with the symptoms of PMS was more effective than that with bromocryptine in relieving autonomic disorders (p < 0.05). Adverse events (AEs) occurred more commonly in the patients receiving bromocriptine (60%); AEs were noted in 7% in the Mastodynon® group (p < 0.05). Conclusion. Mastodynon® that contains Vitex agnus-castus extract is an effective agent with a high safety profile to treat mastalgia and symptoms of PMS in patients with different forms of diffuse mastopathy during the menopausal transition period.